Temeljenje - Jelušič, Primož (2021)
Foundation Engineering. The objective of this book is to present the basic procedures for the design of geotechnical structures. Basic knowledge of soil mechanics is desirable for understanding this textbook. Theoretical knowledge is applied to practical examples. The design of geotechnical structures is carried out according to the standard SIST EN 1997, so the book is also a useful tool for civil engineers in practice. The content of the book is divided into 6 chapters: Bearing capacity of foundations, Earth pressures, Stability of earth retaining structures, Embedded retaining structures, Geotechnical anchors and Piles.
Keywords: foundation enigineering; shallow foundations; earth pressures; earth-retaining structures; deep foundation; geotechnic